Gambaran Kondisi Gingiva Berdasarkan Jenis Kelamin pada Siswa-Siswi SMPN 1 Lubuk Sikaping Kanagarian Pauh Kecamatan Lubuk Sikaping Kabupaten Pasaman Timur - Annisa Monifa Rahmah; Syukra Alhamda (CV. CENDIKIA JENIUS INDONESIA, 2023)
Dental and oral health problems are often encountered in Indonesian society, especially in teenage boys and girls. This study aims to determine the description of gingival conditions based on gender in students at SMPN 1 Kanagarian Pauh, Lubuk Suhuing District, East Pasaman Regency. This research uses a